TRPV4 channels stimulate Ca(2)(+)-induced Ca(2+) release in astrocytic endfeet and amplify neurovascular coupling responses - Dunn, Kathryn M. (National Academy of Sciences, 2013)
In the CNS, astrocytes are sensory and regulatory hubs that play important roles in cerebral homeostatic processes, including matching local cerebral blood flow to neuronal metabolism (neurovascular coupling). These cells possess a highly branched network of processes that project from the soma to neuronal synapses as well as to arterioles and capillaries, where they terminate in “endfeet” that encase the blood vessels. Ca(2+) signaling within the endfoot mediates neurovascular coupling; thus, these functional microdomains control vascular tone and local perfusion in the brain. Transient receptor potential vanilloid 4 (TRPV4) channels—nonselective cation channels with considerable Ca(2+) conductance—have been identified in astrocytes, but their function is largely unknown. We sought to characterize the influence of TRPV4 channels on Ca(2+) dynamics in the astrocytic endfoot microdomain and assess their role in neurovascular coupling. We identified local TRPV4-mediated Ca(2+) oscillations in endfeet and further found that TRPV4 Ca(2+) signals are amplified and propagated by Ca(2+)-induced Ca(2+) release from inositol trisphosphate receptors (IP(3)Rs). Moreover, TRPV4-mediated Ca(2+) influx contributes to the endfoot Ca(2+) response to neuronal activation, enhancing the accompanying vasodilation. Our results identify a dynamic synergy between TRPV4 channels and IP(3)Rs in astrocyte endfeet and demonstrate that TRPV4 channels are engaged in and contribute to neurovascular coupling.